Relationship between physical activity and pain sensitivity in healthy females - Reboya, Carlandra Destiny 1998- (College of Human Kinetics, University of the Philippines Diliman, 2020)
This research aims to analyze the relationship between physical activity and pain sensitivity. Given the higher pain prevalence and pain reports among women than men, this aims to determine whether measures of pain sensitivity-- (1)pain threshold, (2)pain tolerance, and (3)pain intensity are associated with physical activity in healthy women. Twenty-eight healthy females (age range=18-22yrs) participated in the study. Total METs of each participant were measured through the International Physical Activity Questionnaire (IPAQ) short last 7 days format to quantify their physical activity. Participants' pain sensitivity was measured through the Cold Pressor Task (CPT). an experimental technique for inducing pain in humans. It involves placing a hand in cold water and monitoring through a stopwatch and participants' signal to the researcher. A desk bell was used as a tool to ensure uniformity of the signal reported by each participant. Pain threshold was determined by the time the participant was exposed to the painful stimulus, which was when the participant had fully immersed her hand in the cold water set up, until the participant reported pain by pressing the bell. Pain tolerance was determined as the duration of time from the time the participant reported pain until the time the participant reported the need to withdraw her hand by ringing the bell for the second time. Pain perception was rated through Wong-Baker FACES pain scale right after the cold pressor task. Results how that physical activity does not have any significant relationship with pain sensitivity measures namely: pain threshold, pain tolerance, and pain intensity in healthy women. With pain being a multidimensional experience, physiological and psychological factors go hand in hand with pain experience and therefore, both aspects should be considered.